The Effect of Business Strategy on the Performance of MSMEs in Malang City - Novirin, Barli; Soesilowati, Etty; Farida Rahmawati, Farida Rahmawati (Journal of Applied Business, Taxation and Economics Research, 2024)
The purpose of this study was to determine and analyze the effect of business strategy on the performance of MSMEs in Malang City. This research is a quantitative study with variables of business strategy and MSME performance. The research data were collected by interview, documentation, observation, and distributing questionnaires to 30 business scale respondents using a cluster random sampling technique. Data analysis used is multiple linear regression analysis and hypothesis testing. The results prove that business strategy has a positive influence on the performance of MSMEs in Malang City. This shows that business strategy can be used as a basis for consideration in improving the performance of MSMEs in Malang City. This is because the business strategy carried out can improve the performance of MSMEs.